Identifying gram-positive cocci in dermatoscopes and smartphone adapters using MALDI-TOF MS: a cross-sectional study, - Maurício de Quadros; Roberto Carlos Freitas Bugs; Renata de Oliveira Soares; Adriana Medianeira Rossato; Lisiane da Luz Rocha; Pedro Alves d'Azevedo (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: The increasingly frequent use of dermoscopy makes us think about the possibility of transfer of microorganisms, through the dermatoscope, between doctor and patients. Objectives: To identify the most frequent gram-positive cocci in dermatoscopes and smartphone adapters, as well as the resistance profile, and to evaluate the factors associated with a higher risk of bacterial contamination of the dermatoscopes. Methods: A cross-sectional study was carried out with 118 dermatologists from Porto Alegre/Brazil between September 2017 and July 2018. Gram-positive cocci were identified by MALDI-TOF MS and habits of use of the dermatoscope were evaluated through an anonymous questionnaire. Results: Of the dermatoscopes analysed, 46.6% had growth of gram-positive cocci on the lens and 37.3% on the on/off button. The microorganisms most frequently found were S. epidermidis, S. hominis and S. warneri. Attending a hospital, using the dermatoscope at the hospital, with inpatients and in the intensive care unit were significantly associated with colonisation by gram-positive cocci. The highest resistance rates were observed for penicillin, erythromycin and sulfamethoxazole-trimethoprim. Study limitations: The non-search of gram-negative bacilli, fungi and viruses. Moreover, the small number of adapters did not make it possible to better define if the frequency differences were statistically significant. Conclusion: Coagulase-negative staphylococci were frequently identified. S. aureus was detected only on the lens.